I Got the Poison, I Got the Remedy: Healthcare Serial Killers: Healthcare Serial Killers - Tırmıkçıoğlu, Zeynep (The Bulletin of Legal Medicine, 2021)
Objective: Killing with poison or high-dose drug is an uncommon method used in serial murders. Healthcare serial killers differ from classical serial killers because they frequently use high-dose drugs or poison to kill the victims. In the study, it was aimed to create the most up-to-date list of healthcare serial killers and poisons used.Materials and Methods: The internet-based databases were used, and a comparative literature review was conducted. Serial killers using poison or high-dose drug as murder weapons were selected and evaluated.Results: Of the 53 serial killers analyzed, 41 were nurses, 6 physicians, and 6 medical assistants. All physicians and almost all medical assistants were men. In nurses, the male-female gender distribution was almost equal. The median number of victims was 12, and 8 murderers killed 100 or more victims. Morphine (9/53), insulin (7/53), potassium chloride (6/53), succinylcholine (6/53) and lidocaine (6/53) were the most commonly used drugs in murders. Other sedatives, nondepolarizing muscle relaxants such as vecuronium, pancuronium and mivacurium, digoxin, epinephrine, heparin, arsenic and cyanide were also among the poisons and high-dose drugs used. About half (25/53) of serial killers killed their victims using one poison or one drug. Morphine, insulin, potassium chloride, succinylcholine and lidocaine were often used as the single drug in murders.Conclusion: All serial killers examined in the study used their drug knowledge and authority to commit murder. It is remarkable that most of the murderers did not have a pre-identified psychiatric disorder, and they were not suspicious or even considered reliable.
Keywords: serial killer; serial murder; healthcare; poison; high dose; drug